Penatalaksanan Pemeriksaan CT Scan Abdomen Dengan Kontras Dengan Klinis Tumor Padat Ovarium Di Instalasi Radiologi RSUD Dr. Hi. Abdul Moeloek Provinsi Lampung - Made Yully (Universitas Malahayati Lampung, 2022)
ABSTRACT Pre-survey result obtained from the entire radiological eximination in CT-Scan cases of the abdomen found only 1% of cases with clinical solid ovarian tumors. During the research activities the authors found 129 patients with contrast CT scan during july to september 2019 and there were 1 (one) patient with clinical ovarian solid tumors in the Radiology Installation of hospital Dr. H. Abdul Moeloek Province of Lampung. The purpose of this study was to determine the preparation of an abdominal CT-Scan examination with clinical solid ovarian tumors using contrast media and to determine the results of CT- Scan images with clinical solid ovarian tumors. this study uses descriptive qualitative method. A sample of 1 patient was a patient who underwent an abdominal CT scan using contrast media with clinical solid ovarian tumor in the radiology Installation of Hospital Dr. H. Abdul Moeloek Province of lampung. Data is obtained from literature studies, observations, and interviews. The results of a contrast abdominal CT scan based on the doctor's expertise found that there was a solid tumor in the left lower quadrant meseterium, dd: malignant lymph node, gastrointestinal stromal tumor, desmoid tumor Minimal ascites obtained on axial section. The management of abdominal CT –Scan in contrast to clinical ovarian solid tumorsat the Radiology installation Dr.Hi. abdul moeloek General Hospital in Lampung province is quite effectrive, namely to show abnormalities in the organs to be examined as well as the tissues around them. Keywords: CT- Scan, Abdomen, Ovarian Solid Tumor ABSTRAK Pada hasil pre-survey, didapatkan dari keseluruhan pemeriksaan radiologi pada Kasus CT- Scan Abdomen hanya ditemukan 1% kasus dengan klinis Tumor padat ovarium. Selama melakukan kegiatan penelitian penulis menemukan 129 pasien pemeriksaan CT-Scan Abdomen dengan kontras selama bulan juli s/d september 2019 dan terdapat 1 (satu) orang pasien dengan klinis Tumor padat ovarium di instalasi Radiologi RSUD Dr. H. Abdul Moeloek Provinsi Lampung. Tujuan dari penelitian ini adalah untuk mengetahui persiapan pemeriksaan CT-Scan abdomen dengan kontras dengan klinis tumor padat ovarium,untuk mengetahui teknik pemeriksaan CT-Scan Abdomen dengan kllinis Tumor padat ovarium menggunakan kontras media dan untuk mengetahui hasil gambaran CT-Scan Abdomen dengan klinis Tumor padat ovarium. Penelitian ini menggunakan metode Deskriptif Kualitatif. Sampel sebanyak 1 orang pasien yaitu pasien yang melakukan pemeriksaan CT-Scan Abdomen menggunakan kontras media dengan klinis Tumor padat ovarium di Instalasi Radiologi RSUD Dr.H. Abdul Moeloek provinsi Lampung. Data diperoleh dari studi pustaka, observasi dan wawancara. Hasil dari CT Scan abdomen kontras berdasarkan expertise dokter di dapatkan bahwa adanya Tumor solid di meseterium left lower quadrant, dd: malignant limph node, gastrointestinal stromal tumor, desmoid tumor Ascites minimal yang di dapat pada potongan axial. Penatalaksanaan CT Scan abdomen dengan kontras dengan klinis Tumor padat ovarium di Instalasi Radiologi RSUD Dr. Hi. Abdul Moeloek Provinsi Lampung cukup efektif yaitu untuk memperlihatkan kelainan- kelainan pada organ yang akan di periksa serta jaringan di sekitarnya. Kata Kunci: CT-scan, Abdomen, Tumor Padat Ovarium